The Control of Children’s Crimes in Romania - Arhire, Diana-Elena (Richtmann Publishing, 2012)
The aim of this paper is to provide a general presentation regarding the way how children’s crimes control is made in aRomanian community. Starting with a general presentation of the children’s in conflict with penal law, the vulnerability of the children infront of some factors that may orient them to commit offences, the Romanian legal framework and the tendency of this phenomena in thelast years, I tried to address the following questions: What is used in our days in order to control the children’s crimes? Which are theinstitutions and the actors involved in this control process? In which programs are the juvenile offenders involved and why? Do thenumbers say that we really deal with an increase of this phenomenon? Can we say that Romania has a well defined strategy forcontrolling children’s crimes? In order to find an answer to these questions I used as a research method the semi-structured interviewsand a focus-group in which were involved specialists that are working directly with the juvenile offenders. Their opinions as professionalsand practitioners are important for constructing the image of the Romanian strategy used in a micro-community for controlling children’scrimes. According to recent research in this field I consider the debate of this issue a very important one in order to highlight thenecessity to improve the actual strategies used in controlling juvenile crimes. The conclusions of this paper stress that until nowRomania does not have a well defined strategy used for controlling the crimes committed by juveniles.